The impact of hospital pharmacists’ psychological contracts on medication adherence management: The mediating role of job burnout - Yongyong Luo; Mei Nie; Cheng Chen; Yong He; Xiaoyu Jiang; Jianhua Tang; Ting Zhang; Yang Gu; Fushan Tang (PLoS ONE, 2026)
Background This study examines the relationship between hospital pharmacists’ psychological contracts and their attitudes and behaviors in managing patient medication adherence. The goal is to provide a solid scientific foundation and practical recommendations for improving pharmacists’ involvement in adherence management. Methods A Delphi evaluation, involving pharmacy experts from healthcare institutions, was conducted to refine the Pharmacists’ Attitudes and Behaviors Toward Patient Medication Adherence Management Scale. This scale, alongside other relevant instruments, was used to survey pharmacists working in public healthcare institutions across two cities in Guizhou, China. Results The Attitudes Toward Patient Medication Adherence Management Scale exhibited strong reliability, with a Cronbach’s α coefficient of 0.796 and a KMO value of 0.899. The Behaviors Toward Patient Medication Adherence Management Scale demonstrated even higher reliability, with a Cronbach’s α of 0.986 and a KMO value of 0.963. A significant positive correlation was found between pharmacists’ psychological contracts and their attitudes and behaviors toward patient medication adherence management (P < 0.01). Additionally, job burnout was identified as a partial mediator, accounting for 23.41% of the total effect; Targeted interventions to strengthen psychological contracts should be implemented to improve pharmacists’ motivation and performance, ultimately boosting patient safety and treatment outcomes. Conclusions The fulfillment of pharmacists’ psychological contracts plays a key role in enhancing their involvement in medication adherence management. Targeted interventions to strengthen these psychological contracts should be implemented to improve pharmacists’ motivation and performance, ultimately boosting patient safety and treatment outcomes.